Editorial Vol.4(2) - Badal, Bharat Prasad (Research Nepal Journal of Development Studies, 2021)
Development is essentially an aspiration of people for a better future of community from a social, economic, political, cultural, and environmental perspective. Development is the prosperity of people of the planet with peaceful global partnership in the local context. Development is freedom as Prof. Amartya Sen coins. Now the development is itself a sustainable development. Development is not compromised but enlargement of social choices. Development is a significant positive change in humanity. Development is easy to access to food, shelter, clothes, health, education, job, transportation, communication, entertainment, and social security with democratic freedom. Development is simply the fulfillment of basic needs. Development is a basic or fundamental human right. Every man and woman has the right to live a decent life. The planet or nature has provided natural resources equally. Sunlight, rain, river, forest, oxygen many important natural resources are free but land and drinking water are not free. In urban cities, nothing is free even a human has to buy a job to survive. As Mahatma Gandhi says there is enough in nature for the needs of the people but not for greed. Everything is driven by the unlimited wants of a human being. How many resources a do man need? The richest people on the planet are not happy. 25 % of global resources are in the hand of the 80 richest people. Oxfam International published a shocking report in 2017 that only 8 richest people on the planet own 50% of its wealth. Inequality kills. In a day 21000 people die on the planet due to poverty. In every 4 seconds, one person has to die in 2022. A human soul, child of almighty, has to die with starvation in 2022. It is anti-development. It is against Robert Chamber’s idea of putting the last first. Millions of economists and policy-making leaders are working day and night to balance the inequality but the gap is increasing day by day. The cold war is ended. China and USA are both developing in the capitalistic mode of production. The Marxist philosophy with mixed socialism –communism does not exist except in Cuba and North Korea. The next generation has to follow scientific capitalism with sufficient intervention of government. It will be the middle way path of communism and capitalism. As Francis Fukuyama says at the end of history 30 years back chronic capitalism, identity politics, and communism are ending. The modernization is ending. The history is ending for a new just-full, peaceful, and prosperous planet by the people. The scientific mathematics is ending. Two plus two is not limited to four but being five or six. It is the time of deconstruction of modernization. It is a time of paradigm shift. It is time to back to nature and relax. The economic battle is simply up to the grave. It is an issue of good governance and happy life. Development is of course happiness. Development is freedom from future insecurities. It is possible if we can maintain good governance in our mechanism. The land is the gift of nature as water and air must be returned to nature. Let’s enjoy life. Enjoy every bit of time. It is fine simply to be a man, a human being, not any identity politics. The “Research Nepal Journal of Development Studies” welcomes comments, advice, and suggestions from all sectors from its quality improvement and sustainability. We highly acknowledge Prof. Dr. Chandralal Shrestha, Prof. Dr. Jibraj Pokharel, Prof. Dr. Prem Sharma, and Dr. Bharat Prasad Badal, for their contribution to the peer-review process. Mr. Kiran Shrestha and Designer Mr. Binod Ghimire their effort to manage articles of this journal. Similarly, we acknowledge the entire colleagues of the Central Department of Rural Development, Tribhuvan University, Research Nepal, University Grants Commission, teachers, students, contributors, and others for their support and encouragement for the betterment of the journal in the future. Editor in Chief Dr. BHARAT PRASAD BADAL December 2021